Techniques Used in Translation Phrasal Verbs in The Subtitle of “The Devil Wears Prada” - Azzahra, Hasna; Hilman, Evert H. (IKIP Siliwangi, 2025)
This study aims to determine the translation techniques applied to phrasal verbs in the subtitles of The Devil Wears Prada. The qualitative approach is employed to analyze the translation of phrasal verbs, using the primary theory by Molina and Albir’s (2002). The study categorizes phrasal verbs into three types: intransitive, transitive separable, and transitive inseparable, with three examples from each category, consisting of nine verbs. The study identifies the use of six techniques from Molina and Albir’s eighteen proposed methods: (1) one Reduction, 3 (three) Established Equivalent, 3 (three) Literal Translation, (1) one Modulation, (1) one Generalization, and (1) one Substitution. This study on translating phrasal verbs in The Devil Wears Prada provides key insights into the translation techniques used in the film, offering practical guidance for translators and advancing our understanding of cross-cultural adaptation in subtitling.